Penggunaan buku saku SD (Stop Dehidrasi) dalam mencegah dehidrasi pada remaja - Juartika, Wella; Feri, Jhon (Nur Science Institute, 2024)
Dehydration in adolescents is one of the things that can affect the concentration of adolescents during education and other activities. This condition can cause the body not to function normally. Dehydration itself is often thought of as simple thirst. In fact, if not appropriately treated, dehydration can develop into more serious, such as hypovolemia. Based on this, activities are needed that can overcome the level of knowledge of adolescents in overcoming and preventing dehydration. The SD Pocket Book (Stop Dehydration) is a media that contains information on how to calculate fluid needs, how to drink well, and signs of dehydration experienced by adolescents, as well as a checklist of signs of dehydration as an illustration so that adolescents can understand the actions that need to be taken before being taken to the hospital or that can be done alone at home. SMP 2 N Lubuklinggau is one of the junior high schools located in the working area of the Citra Medika Health Center at a distance of 5 KM from the Puskemas. The implementation and evaluation have been carried out from June to September 2023. The results of the evaluation carried out increased knowledge and decreased the number of visits to the School Health Unit (UKS).